(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: the quality of human resources holds an important role, because people involved in a flight not just pilots, but also of other officers, including those responsible for the handling and inspection of aircraft research objectives this is to find out the flight safety supervision of Sam Ratulangi Airport by the Airport Authority Region VIII Manado. This research uses qualitative approach method. This research is focused on the efforts and actions undertaken to achieve aviation safety at the airport, both preventive (preventive supervision) as well as the repressive nature of the (repressive supervision). Informants in this study is taken from the elements directly related to aviation activities at the airport: Airport Authority, airlines, and passengers on the plane. The results showed that the repressive surveillance carried out by doing the monitoring, inspection, and direct assessment of all aspects/fields related to aviation safety at the airport be scope the duties and functions of the Office of the Airport Authority Region VIII Manado as flight safety, aircraft, flight navigation services activities, the fulfilment of standards certification flight navigation areas, emergency response documents aviation security, the implementation of permit approval routes to and from airports, satisfy the standards activities of the Airport related services, service air freight activities, implementation of the Flight Approval (FA), the implementation of permit route, implementation of air transport fares, and against environmental management of airports. Repressive supervision over all aspects related to the safety of the flight not been fullest. The constraints of the repressive surveillance also is the limited human resources Office of the Airport Authority Region VIII Manado either in quantity or quality, of the means of implementing surveillance infrastructure is not yet fully available/are met; and coordination with related parties has not been fully realized properly. The implications of the results of such research is the need to increase the number of employees of the Office of the Airport Authority Region VIII Manado, improve the quality of human resources officers, and improve coordination with the best there is at the airport, The study also shows that although the oversight of aviation safety Sam Ratulangi Airport by the Airport Authority Region VIII Manado is still not a maximum, but with preventive and repressive supervision performed during this have been able to improve flight safety guarantees. Based on the research of aviation safety assurance at Sam Ratulangi airport, makin good as realized by decreasing the number of accidents of air transportation; decrease in the level of air transport security disruptions; increasing the performance of the service of air transportation facilities and infrastructure; and increasing air transportation service. This means that if the role of the Office of the Airport Authority in the oversight of aviation safety can be enhanced or maximized, then certain flight safety will come true better yet. Keywords: surveillance, aviation safety, the Airport Authority